Clinical characteristics and treatment outcomes of patients with insulinoma–a single center's experience of 76 cases over a 10-year period - Wei Li; Yali Cheng; Qingyong Ma; Zheng Wu; Zheng Wang (Heliyon)
Objective: Insulinoma is a rare pancreatic neuroendocrine neoplasm caused by pancreatic beta cell tumor or beta cell proliferation resulting in excessive insulin secretion. Due to its rarity, surgical analysis and summary studies on patients with insulinoma are few and the sample size is limited. Methods: In this study, we retrospective the cumulative experiences including demographics, clinical characteristics, detailed surgical reports and postoperative outcome of 76 patients diagnosed with insulinoma from 2010 to 2020 at the First Affiliated Hospital of Xi'an Jiaotong University. Results: Our cohort consisted of 48 females and 28 males with an average diagnosis age of 52 years. Loss of consciousness (68 %), sweating (59 %), vertigo (56 %) are three most shown symptoms. The average time from symptom onset to diagnosis of insulinoma was 33.4 month. When CT combined with MRI was used, the diagnostic rate was as high as 96.87 %. Of the 76 patients, 48.68 % of preoperative tumors were in the head/neck, and the remaining 51.32 % were in the body/tail. Most of the patients received surgery for enucleation (65.79 %). The duration of surgery was 216 ± 105 min. The incidence of postoperative pancreatic fistula was 53.95 %. Postoperative pancreatic hemorrhage occurred in 6 patients (7.89 %), all of whom were pancreatic head/neck surgery patients. The incidence of pancreatic fistula, bleeding and major complications after the operation of pancreatic head/neck insulinoma was higher than that of pancreatic body/tail insulinoma. Conclusion: CT combined with MRI can localize insulinoma in most patients. As a parenchyma-sparing pancreatectomy, enucleation is the procedure of choice if possible. The incidence of postoperative hemorrhage should be more vigilant after the surgery of pancreatic head/neck insulinoma. The intraoperative suture of high-risk vessels prone to bleeding should be performed if necessary.